APPLICATION OF LOW TEMPERATURE EXPOSURE IN LAPAROSCOPIC SURGERY ON HEPATOBILEAR SYSTEM - Bychkov, S.О.; Grynyov, R.М.; Duchik, L.N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
After the carried out experimental researches authors submit experience of performance 101 laparoscopic operation on organs of hepatobilear system with application of low temperatures influences. For cryoinfluences it was used the own designed cryoapplicator. The analysis of the received results allows to recommend more wide using of low temperatures at laparoscopic operations.